2013
DOI: 10.1089/vbz.2012.1293
|View full text |Cite
|
Sign up to set email alerts
|

Is Dirofilaria repens Endemic in the Havelland District in Brandenburg, Germany?

Abstract: In Brandenburg, northeastern Germany, an outbreak of zoonotic Dirofilaria repens in a sledge dog kennel was detected in January, 2012. Using the modified Knott test, 8 out of 28 adult dogs were microfilaria positive. A D. repens-specific PCR based on the internal transcribed spacer 2 region detected filarial DNA in 11 of these dogs. Northeastern Germany is currently considered to be free of Dirofilaria. The 39% prevalence within the kennel and the fact that the dogs transiently stayed in endemic areas only dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Until recently, central Europe, including Germany, was not considered a region in which D. repens is endemic. However, the recent finding of D. repens-infected dogs and mosquitoes in east Germany in the federal state of Brandenburg (which is located next to Saxony-Anhalt) [11,12], as well as infected mosquitoes in southwest Germany [13] suggested that stable transmission of D. repens is already taking place in Germany as the northernmost transmission area in Europe so far [11,12]. The present case of an autochthonous human infection in east Germany lends further support to this notion.…”
Section: Introductionsupporting
confidence: 65%
“…Until recently, central Europe, including Germany, was not considered a region in which D. repens is endemic. However, the recent finding of D. repens-infected dogs and mosquitoes in east Germany in the federal state of Brandenburg (which is located next to Saxony-Anhalt) [11,12], as well as infected mosquitoes in southwest Germany [13] suggested that stable transmission of D. repens is already taking place in Germany as the northernmost transmission area in Europe so far [11,12]. The present case of an autochthonous human infection in east Germany lends further support to this notion.…”
Section: Introductionsupporting
confidence: 65%
“…In the federal state of Brandenburg in Germany, conditions for larval development were predicted to be sufficient in each of the past 12 years. These projections, together with our finding of mosquitoes carrying D. repens in Brandenburg in 2 successive years and the recurrent detection of infected dogs in this area ( 8 ), present a strong case for the existence of stable local transmission of D. repens in this region of Germany.…”
supporting
confidence: 52%
“…However, a survey in 44 hunting dogs from the Upper Rhine region showed that 3 animals were positive for D. repens microfilariae ( 7 ). In addition, testing of a kennel of sled dogs located in the federal state of Brandenburg, near Berlin, found 8 of 28 animals were infected with the parasite ( 8 ). …”
mentioning
confidence: 99%
“…In the Berlin/Brandenburg area, D . repens positive sledge dogs were presumed to represent autochthonous cases [ 42 , 43 ]. Very recently, an autochthonous canine case was postulated in central Germany [ 44 ].…”
Section: Introductionmentioning
confidence: 99%